Charge transport behavior in gamma‐ray irradiated poly(ethylene terephthalate) estimated by surface potential decay. Issue 3 (27th October 2020) - Gao, Yu; Li, Nan; Li, Jing; Du, Boxue; Liu, Ziyang
Abstract: This study reports on the variation in charge transport behaviour of poly (ethylene terephthalate) (PET) caused by gamma‐ray irradiation estimated by means of surface potential decay (SPD) measurement. The 100 µm‐thick PET specimens were exposed to 60 Co gamma rays to a maximum total dose of 1000 kGy. The SPD test was carried out to obtain charge transport related parameters via various models, and the effect of gamma‐ray on the transport behaviour was examined. Furthermore, Fourier transform infrared spectrum, gel content, ultraviolet‐visible spectroscopy, X‐ray photoelectron spectroscopy, differential scanning calorimetry and polarized optical microscope were employed to characterize the change in material structure induced by the irradiation. The test results indicated that with the growth in the total dose, the deep trap centre was basically unchanged, whereas the shallow trap centre became shallower. In addition, the trap density tended to decrease. The carrier mobility in PET increased with the total dose, and the charge transport manner conformed well to the hopping model. It is suggested that the formation of oxygen‐based groups from the irradiation induced oxidation reaction tends to encourage the charge transport, while the decrease of amorphous region gives rise to the reduction in trap density.